UNVEILING THE NEXUS BETWEEN PREECLAMPSIA AND NUTRITION: A COMPREHENSIVE LITERATURE REVIEW ON MATERNAL HEALTH - Alvian Mohamad Yapanto; Khairani Ayu Lestari; Halin Aliyyu; Eldita Luthfia Tumeko; Shella Setiani; Sandhia Aidhitya; Rika Ferlianti (Universitas Negeri Gorontalo, 2023)
Preeclampsia, a pregnancy-related syndrome impacting multiple organ systems, is a leading cause of maternal mortality, bleeding, and infection. The World Health Organization estimates that preeclampsia contributes to 70,000 maternal and 500,000 infant deaths annually worldwide. Recent research highlights the importance of optimal nutrition from preconception through childhood and adolescence. The novelty of this research is that it examines the relationship between preeclampsia and food: a comprehensive literature review of maternal health. This literature review collected and analyzed articles from online databases to explore the role of micronutrient supplementation in preventing preeclampsia. Findings emphasize the potential benefits of micronutrient supplementation, including L-arginine, vitamin D, and folic acid. Recommendations include daily vitamin D supplementation of 10-25 µg for pregnant women, oral administration of 3g per day of L-arginine for 3 weeks, and high-dose folic acid (4 mg/day) during the first trimester of pregnancy along with multivitamin supplementation. Micronutrient supplements and consuming nutrient-rich foods during pregnancy have been proposed to reduce the likelihood of developing preeclampsia. These approaches can potentially impact the formation of the placenta, oxidative stress levels, and the expression of angiogenic factors. This review underscores the importance of optimal nutrition throughout preconception, pregnancy, birth, and beyond for maternal and infant health. It highlights the need for further research and policy attention in this area. Implementing recommended micronutrient supplementation strategies during pregnancy may contribute to improved maternal and infant outcomes and should be considered as part of a comprehensive prenatal care program.